Peningkatan Hasil Belajar Sejarah Melalui Penerapan Model Pembelajaran Kooperatif Tipe Lottery Card Pada Peserta Didik Kelas XI IPS di SMA Negeri Oinlasi - Missa, Tirsa Marteda; Djakariah, Djakariah; Dethan, Delsy A (FLORESIENSIS, 2024)
This study aims to improve student learning activities and learning outcomes in history, particularly in the material on the arrival of Japan in Indonesia, through the use of the lottery card cooperative learning model. The type of research used is classroom action research (CAR). With the use of the lottery card learning model in this learning process, it can be seen that the classroom action research (CAR) conducted shows the percentage of scores obtained in each cycle. Thus, the conclusion of this study is that the use of the lottery card cooperative learning model can improve the history learning outcomes of students in class XI IPS 2 at Oinlasi State High School.